The role of the principal in fostering al-akhlaq al-karimah among students at smait darul rasyid, east lampung - Chusnul Jauhari; Kharis Syuhud Mujahada; Ahmad Ahadi; Youcha Alassane Touré (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
Globalization has brought widespread Western cultural influences into Indonesia, creating both positive and negative impacts on students, particularly in the realm of moral development. School principals hold a strategic role in mitigating moral degradation by strengthening school-based character formation. This study aims to examine: (1) the current moral condition of students at SMAIT Darul Rasyid East Lampung, (2) the principal’s role in fostering students’ moral character, and (3) the supporting and inhibiting factors influencing moral development at the school. Using a descriptive qualitative method, data were collected through observations, interviews, and documentation, then analyzed through data interpretation. The findings show that several moral issues remain, especially in students’ discipline and practice of the 5S culture (Smile, Greet, Salute, Politeness, Courtesy). The principal plays a significant role through school culture by fulfilling seven leadership functions: educator, manager, administrator, supervisor, leader, innovator, and motivator, implemented in programs such as Dhuha prayer, short religious talks, Qur’an recitation, routine prayers, and ceremonial activities. Supporting factors include strong teacher involvement and community participation, while inhibiting factors relate to students’ individual characteristics and limited understanding of moral and ethical values (akhlaqul karimah).